Lingual dominants of dialogic organizing of written scientific and educational texts - Шабуніна, Вікторія Валентинівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
Certain genres of written form of scientific and educational substyle existence are characterized in the article; communicative intentions of an author of technical educational texts are defined. It is confirmed that interrogative sentences, another’s speech, followed by evaluating of statements, imperative mood, imperative sentences as an appeal to the reader, evaluation verbal means, introductory words and sentences pointing out the expression of the author’s attitude to the information, or having a reference only, as well as the opposing different opinions on the same issue, using prospection and retrospection categories, diverse means of emphasizing, etc. are the basic means of dialogical organizing of scientific texts, the author of which is a scientist.